Research in Library and Information Science - Tejomurthy, A.; Kumar, P.S.G. (DESIDOC Journal of Library & Information Technology, 2003)
Research in Library and information Science (115) briefly means the collection and analysis of original data on a problem of librarianship done within the library schools according to scientific and scholarly standards. This article briefly describes the research, its need and history, etc in LIS and presents the pattern and state-of-the-art of research in LIS in lndia. The reasons for slow growth in research in LIS in lndia and scanty financial support to it have been explored. Several suggestions to catalyse the research activities in LIS in lndia have been given. It concludes that there are research opportunities and research atmosphere in lndia and the library professionals and LIS faculty should be involved in research to improve information sources and services. http://dx.doi.org/10.14429/dbit.18.1.3382